Blue and Red Light Color Combinations Can Enhance Certain Aspects of Digestive and Anabolic Performance in Juvenile Steelhead Trout Oncorhynchus mykiss - Chen, Xueweijie; Zhou, Yangen; Huang, Jinze; An, Dong; Li, Li; Dong, Yunwei; Gao, Qinfeng; Dong, Shuanglin (Frontiers in Marine Science, 2022)
The light spectrum varies with the altitude of the sun and shows different light colors in clear water. To investigate the response of juvenile steelhead trout Oncorhynchus mykiss (initial weight, 34.67 ± 2.69 g) under different light color conditions, we assessed the effects of different blue and red light color combinations on plasma biochemical parameters, digestive enzyme activity, and RNA/DNA ratio in trout over 16 weeks. The trial was designed with six treatments in which the light color varied at a constant light intensity of 150 lx: 12 h white light then 12 h dark (12W), 12 h blue light then 12 h dark (12B), 12 h red light then 12 h dark (12R), 1.5 h blue light and 9 h red light and 1.5 h blue light then 12 h dark (3B9R), 3 h blue light and 6 h red light and 3 h blue light then 12 h dark (6B6R), and mixing for 12 h of blue and red light and 12 h dark (T12BR). The results revealed that the 3B9R light environment significantly increased total plasma protein (TP) levels, enhanced the activity of midgut lipase, trypsin, and gastric lipase, and increased RNA content in the liver and muscle tissue to promote protein synthesis efficiency, thereby improving digestive and anabolic performance. This indicates that steelhead trout have adapted well to such variable light conditions during the long-term evolution process. In contrast, trout exposed to the 6B6R light environment showed significant reductions in plasma glucose, TP, and triglyceride levels, decreased activity of gastrointestinal digestive enzymes, and reduced protein synthesis capacity in the muscle and liver, resulting in weakened digestive and anabolic performance. Furthermore, despite the high RNA content and RNA/DNA ratio in a 12R light environment, relatively high plasma cholesterol and triglycerides levels were observed, which might indicate the presence of oxidative stress. Therefore, this light is not considered suitable for long-term cultivation. Thus, the 3B9R light environment can be used to improve the digestive and anabolic performance of steelhead trout.